Urban Flood Impact Assessment for the Electricity Supply Industry in Malaysia - Rostam N.E.B.; Mohd Sidek L.; Marufuzzaman M.; Fai C.M.; Basri H.; Ahmad R.D.R.; Hayder G. (Springer, 2023)
Flooding has become one of the most rapidly growing types of natural disasters that have spread around the globe. In December 2014, 21 fatalities cases have been recorded and more than 200,000 people have been evacuated in Malaysia due to flood. Tenaga Nasional Berhad (TNB) has provided the structure mitigation for their substations after their assets been affected by the flood. This research identified the flood risk impact on the electricity supply industries in Malaysia by using TNB as the case study. Therefore, the main objective of this study is to identify the substation that exposed to flood risk at the Klang river basin and the possible mitigation measures to reduce the flooding impact. The flood risk assessment has been conducted by overlay the existing flood hazard map for the Klang river basin by using ArcGIS. The results showed that 473 TNBs substations located in flood-prone for 100-years ARIs. After doing several discussions with TNB Distribution, the research identified the suitable mitigation measures and estimated value on mitigation costs needed to protect the substation. Based on this study, a simple guideline has been developed for TNB management for their future planning. 2020, Springer Nature Singapore Pte Ltd.